2014
DOI: 10.1161/hypertensionaha.113.01667
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Cerebral Autoregulation in Pregnancy and the Risk of Preeclampsia

Abstract: Abstract-Preeclampsia may affect severely the cerebral circulation leading to impairment of cerebral autoregulation, edema, and ischemia. It is not known whether impaired autoregulation occurs before the clinical onset of preeclampsia, and whether this can predict the occurrence of preeclampsia. Seventy-two women at 25 to 28 weeks of gestation were studied. Control values were derived from 26 nonpregnant women. Dynamic properties of cerebral autoregulation (DCA) were measured in the middle and posterior cerebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 32 publications
(34 reference statements)
1
18
0
2
Order By: Relevance
“…For example, Zunker et al reported increased CBF velocities in the middle cerebral arteries of patients with preeclampsia or eclampsia (Zunker et al 1995). Moreover, patients who had preeclampsia in a previous pregnancy had poor dynamic CBF autoregulation (Janzarik et al 2014). A small clinical study showed that 46% of preeclamptic and eclamptic patients studied exhibited cortical and/or subcortical lesions involving the occipital lobe; 72% of which had a watershed distribution that was hypothesized to result from acute fluctuations in blood pressure (Demirtas ß et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Zunker et al reported increased CBF velocities in the middle cerebral arteries of patients with preeclampsia or eclampsia (Zunker et al 1995). Moreover, patients who had preeclampsia in a previous pregnancy had poor dynamic CBF autoregulation (Janzarik et al 2014). A small clinical study showed that 46% of preeclamptic and eclamptic patients studied exhibited cortical and/or subcortical lesions involving the occipital lobe; 72% of which had a watershed distribution that was hypothesized to result from acute fluctuations in blood pressure (Demirtas ß et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies used animal models of pregnancy since such measurements in pregnant women are challenging and potentially dangerous. Studies in humans using non-invasive techniques to measure dynamic autoregulation during normal pregnancy have found improved or no change in CBF autoregulation in pregnant compared with nonpregnant women (47). To our knowledge, no study has determined the limits of CBF autoregulation during pregnancy, but it is important to understand because of the potential for acute hypotensive and hypertensive episodes that exist, especially during parturition.…”
Section: Cbf Autoregulation and Hemodynamicsmentioning
confidence: 99%
“…It was suggested that this might explain why eclampsia can occur even without increases in blood pressure, van Veen et al (2013). In fact, phase (but not gain) has been found to be significantly higher in pregnant (25-28 weeks) women, compared to normal subjects, Janzarik et al (2014). In fact, phase (but not gain) has been found to be significantly higher in pregnant (25-28 weeks) women, compared to normal subjects, Janzarik et al (2014).…”
Section: Pregnancymentioning
confidence: 99%